2019
DOI: 10.21139/wej.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the hydraulic efficiency of a constructed wetland

Abstract: Measurement of the efficiency of constructed wetlands is critical for maintenance of their functions and contribution to improving water quality in urban areas. A fluorescent dye tracer, Rhodamine-WT, was used to track water flow through a stormwater-reliant, free water surface (FWS) constructed wetland in a Mediterranean climate. The mean hydraulic residence time (HRT) was calculated and compared to the design HRT, in order to gain an appreciation of the hydraulic efficiency of the wetland system. The actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…This was considered the optimal alternative from an ecohydrological perspective. Harrington (2019) estimated that the typical required hydraulic retention time (HRT) in a constructed wetland for stormwater management is five days and Blick et al (2004) suggested an average depth of 3 m is required for treatment.…”
Section: Non-traditional Management Alternativesmentioning
confidence: 99%
“…This was considered the optimal alternative from an ecohydrological perspective. Harrington (2019) estimated that the typical required hydraulic retention time (HRT) in a constructed wetland for stormwater management is five days and Blick et al (2004) suggested an average depth of 3 m is required for treatment.…”
Section: Non-traditional Management Alternativesmentioning
confidence: 99%